2013
DOI: 10.1186/1472-6882-13-268
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effects of aged garlic extracts against Aβ-induced neurotoxicity and cognitive impairment

Abstract: BackgroundIn vitro antioxidant activities and neuron-like PC12 cell protective effects of solvent fractions from aged garlic extracts were investigated to evaluate their anti-amnesic functions. Ethyl acetate fractions of aged garlic had higher total phenolics than other fractions.MethodsAntioxidant activities of ethyl acetate fractions from aged garlic were examined using 2,2'-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) diammonium salt (ABTS) and malondialdehyde (MDA) inhibitory effect using mouse whole b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 29 publications
0
32
0
1
Order By: Relevance
“…Specifically, it has been shown that β-amyloid promotes oxidation in several experimental systems (Jeong et al, 2013) and conversely, pro-oxidants increase the production of β-amyloid (Tamagno et al, 2005). Thus, reducing oxidative stress through antioxidant supplementation has received considerable attention as a therapy to retard AD.…”
Section: Introductionmentioning
confidence: 98%
“…Specifically, it has been shown that β-amyloid promotes oxidation in several experimental systems (Jeong et al, 2013) and conversely, pro-oxidants increase the production of β-amyloid (Tamagno et al, 2005). Thus, reducing oxidative stress through antioxidant supplementation has received considerable attention as a therapy to retard AD.…”
Section: Introductionmentioning
confidence: 98%
“…Nillert and collaborators had established a neuronal degenerative model by treatment with 1 μl of aggregated Aβ in the lateral ventricles; eventually they observed that ethanol extract-aged black garlic, a variant form of black garlic produced by aging the fresh garlic in room temperature, could ameliorate short-term recognition memory and inhibit activation of microglia as well as production of IL1β, a proinflammatory cytokine [46]. Additionally, ethyl acetate fraction of aged garlic extract protects PC12 neuron-like cells and ICR mice from neurotoxicity and amnesia induced by Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) [47]. Note that both aged and black garlics are rich of S-allyl-cysteine content, a stable bioactive organosulfur compound which also exerts anti-inflammatory, neuroprotective, and antioxidant effects [48].…”
Section: Neuroprotective Effect Of Black Garlicmentioning
confidence: 99%
“…Afterwards, NaoH 250 μL was added in each well and after 30 min the supernatant was collected and again incubated at 37 . The microplate reader was used for estimation the LDH activity at 450 nm 20,21 .…”
Section: Lactate Dehydrogenase Ldh Release Assaymentioning
confidence: 99%